The Use of Expanded Polystyrene (EPS) Waste on the Compressive Strength of Concrete Using Fiber Reinforced Polymer (FRP) - Rasendriya, Shafa; Effendi, Rizki; Setiawan, Randy; Purnama, Ikhwan Arief (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2026)
The increase in restaurants and online food ordering can increase waste or waste made from Expanded Polystyrene (EPS). Expanded Polystyrene (EPS) can be used as an additive to concrete because it has properties that are difficult to decompose naturally. Along with the development of the times, many innovations have sprung up in the world of construction to increase the strength of structures. The reinforcement of concrete is done by providing alternative materials that are quite popular, namely Fiber Reinforced Polymer (FRP). This study was conducted to determine the physical properties, mechanical properties of concrete, and the percentage of the use of the most optimum additives that will be applied to the foundation structure using additional materials in the form of Expanded Polystyrene (EPS) with variations of 0%, 1%, 1.5%, 2%, and 2.5% and a layer of Fiber Reinforced Polymer (FRP) as much as 1 layer which will be tested compressively, by looking at the effect of two types of water for curing, namely peat water and normal water with a planned concrete quality of 21.7 MPa using a cylindrical concrete mold 15 cm in diameter and 30 cm high. Concrete compressive strength tests were conducted at 7 days and 28 days of concrete age. Based on the test results, there is an increase in the highest water absorption of concrete, namely in the 28-day normal water immersion variation of 2% EPS + FRP by 4.05% The addition of Expanded Polystyrene (EPS) and Fiber Reinforced Polymer (FRP) in concrete can increase the highest concrete compressive strength, namely in the 7-day NORMAL water immersion variation 1.5% EPS + FRP by 27.54 MPa. While the highest concrete strength value in peat water immersion for 7 days of normal variation is 27.10 MPa.